Investigasi pembuatan mikropartikel carbon menggunakan mesin high energy ball milling (HEBM) model shaker mill - Nugroho Tri Tri Atmoko; Bambang Margono; Fariyono Fariyono; Wahyu Purno Satrio (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2023)
The challenge of human civilization is to produce materials that will perform better in the future, so it is necessary to develop new materials. In this research, the process of making carbon particles will be carried out using the high-energy ball milling (HEBM) with shaker mill model. The effect of the shaker mill process on carbon particles for 120 hours on size and morphology will be analyzed through a series of tests. The research began by preparing carbon powder that had been ground and passed through mesh 200. The carbon particles that had passed through mesh 200 were pounded into steel balls (high energy ball milling) using the shaker mill model. A particle size analysis (PSA) test was carried out to measure the dimensions of the carbon particles. In contrast, a scanning electron microscopy (SEM) test was carried out to see the shape and morphology of the carbon particles. The results show that the carbon particles measured before the shaker mill process are 2526.03nm, while the dimensions of the carbon particles will decrease to 608.43 when the shaker is milled for 120 hours. Meanwhile, the shape and morphology of the carbon particles do not appear to be homogeneous. This indicates that the shaker mill process on carbon particles for 120 hours has not reached nano dimensions and is homogeneous.